2020
DOI: 10.1136/bmjopen-2019-029069
|View full text |Cite
|
Sign up to set email alerts
|

Short-term exposure to pollen and the risk of allergic and asthmatic manifestations: a systematic review and meta-analysis

Abstract: BackgroundSeveral studies have assessed effects of short-term exposure to pollen on allergic and asthmatic manifestations. The evidence is inconclusive, and no meta-analysis has been published.ObjectiveTo synthesise the evidence on the relations between short-term pollen exposure and the risk of allergic and asthmatic manifestations.MethodsWe performed a systematic literature search of PubMed and Scopus databases up to the end of August 2018. In addition, we reviewed the reference lists of relevant articles. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 57 publications
(81 reference statements)
2
44
0
Order By: Relevance
“…The patients in our cohort are sensitized to birch pollen and thus experience more severe allergy symptoms when exposed to higher densities of Betula trees. The meta-analysis of Kitinoja et al (2020) confirmed that short term exposure to pollen was associated to an increase in allergic and asthmatic symptoms. On the other hand, we found that Alnus density was inversely associated with severe allergy.…”
Section: Comparisons With Other Studiesmentioning
confidence: 62%
“…The patients in our cohort are sensitized to birch pollen and thus experience more severe allergy symptoms when exposed to higher densities of Betula trees. The meta-analysis of Kitinoja et al (2020) confirmed that short term exposure to pollen was associated to an increase in allergic and asthmatic symptoms. On the other hand, we found that Alnus density was inversely associated with severe allergy.…”
Section: Comparisons With Other Studiesmentioning
confidence: 62%
“…Exposures to pollen from certain trees, grasses and herbs have been associated with some symptoms and signs of allergic reactions among subjects with asthma and allergies. 1 These effects are linked to type I allergic sensitization, which is mediated by specific IgE antibodies in the eyes and upper and lower airways. 2 Daily variation of pollen associates with exacerbations of asthma, and with daily outpatient visits and hospitalizations attributable to asthma and chronic obstructive pulmonary disease (COPD).…”
Section: Introductionmentioning
confidence: 99%
“… 2 Daily variation of pollen associates with exacerbations of asthma, and with daily outpatient visits and hospitalizations attributable to asthma and chronic obstructive pulmonary disease (COPD). 1 , 3 , 4 …”
Section: Introductionmentioning
confidence: 99%
“…However, studies have not managed to show that pollen concentrations have significant correlation with the change of lung function tests in all sorts of pollens. [35][36][37] In a Swedish study, 35 | 699…”
Section: Discussionmentioning
confidence: 99%